Islamic Self Love in Handling Academic Stress of MAN IC Students - Rochanah, Rochanah; Hidayati, Ilmi; Faizah, Naila (IAIN Kudus, 2025)
Islamic Self Love in Handling Academic Stress of MAN IC Students. Academic stress is a number of academic demands faced by students such as assignments, exams and so on while in the school environment. Academic stress will cause pressure and threaten individuals and then cause reactions of discomfort, worry, anxiety and restlessness that will affect their academic performance. The formulation of the problem raised in this research is 1) what causes academic stress in MAN IC students, 2) how is the Islamic Self Love Habitus applied by students as an effort to overcome academic stress. The type of research used in this research is field research. This approach is used as an effort to intensively understand and explore the experiences of individuals so that meaning can be obtained from the phenomenon. The chosen approach uses a qualitative descriptive approach with the aim of knowing the Islamic self-love habitus as an effort to overcome students' academic stress during academic activities. In the research conducted, the selected sources were dormitory assistant teachers, guidance and counseling teachers and MAN students, Pasuruan Scholars. There were four respondents that the researcher interviewed to gather information related to the research theme. The research locus taken was MAN Insan Scholar Pasuruan, East Java. In this research, efforts to collect data were carried out through interviews, observation and documentation. The data analysis technique chosen uses inductive qualitative analysis, namely an analysis based on the data obtained and then reducing the data obtained, presenting the data, drawing conclusions and finally carrying out verification. Data analysis techniques are carried out throught the stages of data reduction, data presentation and drawing conclusions. Based on the description in the discussion, the results that can be concluded are 1) The demands of the students' parents/guardians. 2) The busy schedule of activities at MAN Insan Scholar. 3) Competition for achievement between friends. 4) Demands (pressure) from students' parents. The application of the Islamic Self Love Habitus as an Effort to Overcome Students' Academic Stress is as follows; 1) Get involved in positive activities in the religious sector; Tahfidz Camp Scholar Program and Arbain Nawawi hadith memorization program. 2) Make the best use of the available time. 3) Take advantage of important moments with your creativity. 4) Stop comparing yourself to others. 5) Make friends with people who have a good influence. 6) Be thankful. 7) Be patient.Keywords: Islamic Self-Love, Academic Stress, MAN IC Students.